INTERPERSONAL COMMUNICATION BETWEEN LECTURERS AND STUDENTS IN INFLUENCING STUDENT’S LEARNING MOTIVATION - Munawarah Munawarah; Rina Novianty (MaPan : Jurnal Matematika dan Pembelajaran, 2020)
Abstract:This study is an ex post facto that aimed to determine the effect of interpersonal communication between lecturers and students on the students’ learning motivation. The population included all 4th-semester students at the Department of Sharia and Islamic Economics of State Institute Islamic Institute of Bone, consisting of 210 students with the sample as many as 42 students. The methods of data collection were observation, questionnaires, and documentation. The techniques of data analysis used were descriptive analysis and inferential analysis using a simple linear regression test. Based on the calculation of the questionnaire score, it was known that the significance value obtained at 0.00 was stated to be smaller than the confidence level of 0.05 (0.00 <0.05). Based on the significance value, it can be concluded that H0 was rejected, which means that there was an effect of Interpersonal Communication on the students’ learning motivation. While the R-squared value = 0.650, which means that the effect of interpersonal communication between the lecturers and students to the students’ learning motivation was 65% while 35% of students’ learning motivation was affected by other variables that are not the focus of this study. The results of this study proved that interpersonal communication between lecturers and students consisting of several indicators, namely the attitude of openness, empathy, support, positive attitude, and equality, has a positive effect on the students’ learning motivation.Abstrak:Penelitian ini merupakan penelitian ex post facto, bertujuan untuk mengetahui pengaruh komunikasi interpersonal dosen dan mahasiwa terhadap motivasi belajar mahasiswa. Populasi dalam penelitian ini adalah seluruh mahasiswa semester 4 Jurusan Syariah dan Ekonomi Islam IAIN Bone yang berjumlah 210 mahasiswa dengan sampel sebanyak 42 mahasiswa. Pengambilan data menggunakan metode observasi, angket, dan dokumentasi. Teknik analisis data menggunakan analisis deskriptif dan analisis inferensial menggunakan uji regresi linear sederhana. Berdasarkan perhitungan skor angket diketahui bahwa nilai signifikansi yang diperoleh sebesar 0,00 dinyatakan lebih kecil dari taraf kepercayaan 0,05 (0,00 < 0,05). Berdasarkan nilai signifikansi dapat disimpulkan bahwa H0 ditolak, yang berarti bahwa ada pengaruh komunikasi interpersonal terhadap motivasi belajar mahasiswa. Sementara itu, nilai R Square = 0.650 yang berarti bahwa pengaruh komunikasi interpersonal antara dosen dan mahasiswa terhadap motivasi belajar mahasiswa sebesar 65% sedangkan 35% motivasi belajar mahasiswa dipengaruhi oleh variabel lain yang tidak menjadi fokus pada penelitian ini. Hasil penelitian ini membuktikan bahwa komunikasi interpersonal antara dosen dan mahasiswa yang terdiri dari beberapa indikator yakni adanya sikap keterbukaan, empati, dukungan, sikap positif, dan kesamaan/kesetaraan berpengaruh positif terhadap motivasi belajar mahasiswa.